Physicochemical principles of pharmacy - Florence, A. T. (Alexander Taylor); Attwood, D. (New York : Chapman and Hall, 1988)
This book provides the physicochemical background to the design and use of pharmaceutical dosage forms. It goes beyond the introductory aspects of the subject to show how basic physicochemical principles are essential to an understanding of every aspect of drug action, from the dosage form to the site of action in the body. This is not a textbook of physical chemistry for pharmacists, but is a book which bridges the gap between basic first-year physical chemistry and the more applied practice of later years. This extensively revised second edition includes much new material, illustrations and references to take into account recent scientific developments and curriculum changes.
1. Gases and volatile agents -- 2. Properites of the solid state -- 3. Physicochemical properties of drugs in solution -- 4. Chemical stability of drugs -- 5. Solubility and partitioning of drugs -- 6. Surfactants -- 7. Disperse systems -- 8. Polymers and macromolecules -- 9. Drug absorption and routes of administration -- 10. Drug interactions and incompatibilities: a physicochemical view -- 11. Assessment of dosage forms in vitro.
Includes bibliographies and index.
Keywords: Pharmaceutical chemistry; Physical organic chemistry; Chemistry, Pharmaceutical; Chemistry, Physical; Pharmacy